In Silico Study: Metabolite Compounds of Zingiber Officinale Var. Rubrum as Potential E2F2 Inhibitor Agents in Breast Cancer Signaling Pathway - Khoirunnisa Purwamita Budiutami; Aryo Tedjo; Fadilah Fadilah; Surya Dwira; Ajeng M. Fajrin (Green Publisher Indonesia, 2026)
Breast cancer ranks among the leading causes of death in women, linked to disruptions in signaling pathways regulating cell proliferation and survival, particularly E2F2 gene activity. E2F2 regulation falters when pRB is phosphorylated by Cyclin D–CDK4/6 or Cyclin E–CDK2 complexes, freeing E2F2 to activate cell cycle genes. This study,